Meaning of Antiretroviral Therapy for PLWHA - Sitanggang, Antonij Edimarta; Octavia, Yunida Turisna; Hasibuan, Eva Kartika (Alta Dharma Publisher, 2022)
Background: Human Immunodeficiency virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) are global health problems today. WHO states that there are 35 million people in the world living with HIV/AIDS. This problem occurs due to the management of patients who have not been optimal; control is only concentrated on specific and general therapy by relying on antiretroviral treatment (ARV). The use of antiretrovirals (ARVs) in patients who test positive for HIV is an effort to extend the life expectancy of people living with HIV and AIDS and make them healthier and more productive by reducing viremia and increasing the number of CD4 cells. Objective: This study aims to explore the experience of PLWHA in undergoing ARV therapy in the work area of ??the Helvetia Health Center Medan. Method: This research is qualitative research with a descriptive phenomenological approach. The population of this study was PLWHA, who received ARV in the working area of ??Helvetia Health Center Medan. The number of participants is 6 people, and the data saturation has been achieved and taken using a purposive sampling technique. Data collection method with in-depth interviews. Data were analyzed using the N.Vivo software version 12.0 trial. Result: The research results obtained from the interviews showed that there are 3 themes, 7 sub-themes, and 13 categories. The 3 themes are understanding the meaning of ARV treatment, getting support for taking ARVs, and having hopes related to ARVs. Conclusion: In conclusion, participants in this study went through various stages in obtaining ARVs considering that PLWHA already fully understood the meaning of ARVs that could extend the life expectancy of PLWHA